Pouring material for firing furnaces

A pourable refractory material with controlled silica and CaO content forms a high viscosity glass layer to prevent alkali penetration and physical impacts, addressing hydration and corrosion issues in furnaces.

JP2025062878AActive Publication Date: 2025-04-15KROSAKI HARIMA CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023172234
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-03
Publication Date
2025-04-15
Estimated Expiration
2043-10-03

AI Technical Summary

Technical Problem

Castable refractory materials used in furnaces face issues such as hydration-induced strength increase requiring a drying process, susceptibility to physical impacts, and alkali attack leading to corrosion and peeling.

Method used

A pourable material comprising refractory raw materials with specific ranges of silica flour and colloidal silica content, along with controlled CaO component, to form high viscosity glass on the surface, suppressing alkali penetration and physical impacts.

Benefits of technology

Eliminates the need for a drying process and effectively prevents alkali attack and physical impacts, maintaining structural integrity under furnace conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062878000001
    Figure 2025062878000001
  • Figure 2025062878000002
    Figure 2025062878000002
Patent Text Reader

Abstract

To provide a pouring material for firing furnaces, which does not require a drying process after pour construction, can suppress physical impact from the contents of the furnace, and can suppress alkali attack.SOLUTION: A pouring material for a firing furnace, which is formed by adding 0.5 mass% or more and 5 mass% or less of colloidal silica as a SiO2 component to a refractory raw material mixture, wherein the refractory raw material mixture comprises: a total of 75 mass% or more of one or more of alumina raw material, alumina-silica raw material, and silicon carbide raw material; 1 mass% or more and 15 mass% or less of silica flour; and 0.5 mass% or less (including zero) of a CaO component derived from alumina cement.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pourable material for burning furnaces such as incinerators, fluidized bed furnaces, industrial waste kiln processing furnaces, furnaces for circulating fluidized bed (CFB) boilers, furnaces for cement manufacturing facilities, gasification melting furnaces, and stoker furnaces. [Background technology]

[0002] Castable materials are a general term for unshaped refractories that can be cast, and are also called castable refractories or castables. Such castable materials generally use cement (alumina cement, portland cement, magnesia cement, etc.) as a binder, but when cement is used as a binder, a hydration reaction occurs at room temperature, which increases the strength of the castable body, making it difficult to dehydrate, and there is a risk of explosion when the temperature inside the furnace rises. Therefore, a drying process is required after casting, which is expensive and requires long periods of downtime.

[0003] On the other hand, castable materials using silica sol, i.e., colloidal silica, as a binder are also known (e.g., Patent Documents 1 to 4). However, in a sintering furnace that heat-treats (sinters or incinerates) materials inside the furnace, such as an incinerator, the castable construction material that forms the furnace wall has a problem in that it is susceptible to physical impacts and erosion reactions from the materials inside the furnace that are flowing inside the furnace. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-168596 A [Patent Document 2] JP 2018-111612 A [Patent Document 3] JP 2019-119653 A [Patent Document 4] JP 2019-142727 A Summary of the Invention [Problem to be solved by the invention]

[0005] The inventors conducted a detailed investigation into the corrosion reaction that occurs in a kiln and found that the main cause of the corrosion reaction in the kiln is so-called alkali attack, which is corrosion caused by alkaline components (Na2O, KO, CaO, etc.) originating from the materials inside the kiln. In other words, in the kiln, the working surface (surface of the workpiece) becomes less viscous due to alkali attack, allowing alkali to easily penetrate into the workpiece. As a result, the difference in expansion between the alkali-permeated layer and the non-permeated layer causes peeling, and the corrosion progresses.

[0006] In view of the above, the problem that the present invention aims to solve is to provide a pourable material for firing furnaces that does not require a drying process after pouring, can suppress physical impacts from items inside the furnace, and can suppress alkali attack. [Means for solving the problem]

[0007] The inventors of the present invention conducted repeated tests and research to obtain a means for suppressing alkali penetration due to alkali attack in a casting material using colloidal silica as a binder, and as a result, discovered that it is effective to generate high viscosity glass on the surface (working surface) of the applied body. In order to achieve this, it is important to control the amount of silicate bond in the matrix of the applied body, and specifically, it is important to include silica flower in a specific range of content in the refractory raw material mixture of the casting material and to set the addition rate of colloidal silica as a SiO2 component within a specific range.

[0008] The present invention has been conceived based on these findings and technical ideas, and according to one aspect thereof, there is provided the following pourable material for a firing furnace. A pourable material for a firing furnace, comprising a refractory raw material mixture containing at least one of an alumina raw material, an alumina silica raw material, and a silicon carbide raw material in a total amount of 75% by mass or more, and 1% by mass or more and 15% by mass or less of silica flower, and having a CaO component content of 0.5% by mass or less (including zero) derived from alumina cement, to which colloidal silica is added at an addition rate of 0.5% by mass or more and 5% by mass or less as a SiO2 component. Effect of the Invention

[0009] According to the present invention, a drying process is not required after pouring, and physical impacts from objects inside the furnace can be suppressed, as well as alkali attack. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The pourable material for firing furnaces of the present invention (hereinafter simply referred to as the "pouring material of the present invention") contains a total of 75 mass% or more of one or more of alumina raw materials, alumina silica raw materials, and silicon carbide raw materials, as well as 1 mass% to 15 mass% of silica flower, and has a CaO component content of 0.5 mass% or less (including zero) derived from alumina cement, to which colloidal silica is added at an addition rate of 0.5 mass% to 5 mass% as a SiO2 component.

[0011] Thus, in the pourable material of the present invention, the refractory raw material mixture is characterized by having one or more of an alumina raw material, an alumina silica raw material, and a silicon carbide raw material as the main material, containing 1% by mass or more and 15% by mass or less of silica flour, and having a content of the CaO component derived from alumina cement of 0.5% by mass or less (including zero).

[0012] If the silica flour content is less than 1% by mass, sufficient silicate bonds are not formed in the matrix of the applied body. Therefore, the effect of suppressing alkali penetration and the effect of suppressing physical impact from objects in the furnace cannot be obtained. On the other hand, if the silica flour content exceeds 15% by mass, the applied body becomes excessively dense because the silica flour is a fine powder. Therefore, there is a risk of explosion when the temperature in the furnace rises. In addition, the particle size structure of the refractory raw material mixture becomes excessively fine powder, and the content of aggregate decreases relatively, resulting in a decrease in the compressive strength of the applied body and a decrease in the effect of suppressing physical impact from objects in the furnace. The silica flour content is preferably 3% by mass or more and 10% by mass or less.

[0013] In addition, in the present invention, the content of the CaO component derived from alumina cement in the refractory raw material mixture is limited to 0.5 mass% or less (including zero). This is because the CaO component derived from alumina cement promotes alkali penetration due to alkali attack. Also, as described above, the CaO component derived from alumina cement causes explosion, making a drying process necessary after pouring. From these viewpoints, the lower the content of the CaO component derived from alumina cement, the better, and it is most preferable that it is zero.

[0014] In the pourable material of the present invention, the refractory raw material composition preferably contains calcined alumina in an amount of 4% by mass to 10% by mass. By containing calcined alumina in this range, the body is appropriately densified, improving the effect of suppressing alkali penetration and the effect of suppressing physical impact from the inside of the furnace. Note that, in the present invention, calcined alumina does not correspond to the alumina raw material, which is one of the main materials of the refractory raw material composition. In other words, in the present invention, the content of the alumina raw material does not include the content of calcined alumina.

[0015] As described above, in the present invention, colloidal silica is used as a binder, and its addition rate is 0.5% by mass or more and 5% by mass or less as SiO2 component. If the addition rate of colloidal silica (meaning the addition rate as SiO2 component, the same applies below) is less than 0.5% by mass, sufficient silicate bonds are not formed in the matrix of the applied body. Therefore, the effect of suppressing alkali penetration and the effect of suppressing physical impact from objects in the furnace are insufficient. On the other hand, if the addition rate of colloidal silica exceeds 5% by mass, the porosity of the applied body increases, and the density is excessively reduced, and the compressive strength of the applied body is also reduced. As a result, the effect of suppressing alkali penetration and the effect of suppressing physical impact from objects in the furnace are reduced. It is preferable that the addition rate of colloidal silica is 1.5% by mass or more and 5% by mass or less.

[0016] In this embodiment, colloidal silica is added as a binder to the above-mentioned refractory raw material mixture, but in addition, various additives such as dispersants, hardening regulators, and anti-explosion agents can also be added as appropriate. Dispersants impart fluidity during application, and specific examples include inorganic salts such as sodium tripolyphosphate, sodium hexametaphosphate, sodium ultrapolyphosphate, acidic sodium hexametaphosphate, sodium borate, sodium carbonate, polymetaphosphates, sodium citrate, sodium tartrate, sodium polyacrylate, sodium sulfonate, polycarboxylates, β-naphthalenesulfonates, and naphthalenesulfonic acid. The hardening regulator includes a hardening accelerator and a hardening retarder. Specific examples of hardening accelerators include hydrated lime, calcium chloride, gypsum, magnesia, sodium aluminate, lithium carbonate, etc. Specific examples of hardening retarders include boric acid, oxalic acid, citric acid, gluconic acid, sodium carbonate, sugar, etc. Specific examples of anti-splitters include organic fibers, organic foaming agents, basic aluminum lactate, metallic aluminum, etc. Specific examples of organic fibers include polymeric organic fibers such as vinylon (including polyvinyl alcohol), rayon, polyester, nylon, polypropylene, and polyethylene. These additives, like colloidal silica as a binder, are added in proportions based on 100% by mass of the refractory raw material mixture. The addition rate may be the same as that of general pouring materials.

[0017] In addition to the above refractory raw material mixture, binder, and additive, the castable material of the present invention can also use large coarse particles with a particle size of 8 mm or more. The large coarse particles have the role of preventing the progress of cracks generated in the refractory structure, and as the material thereof, one or more of alumina, alumina silica, and silicon carbide can be used as the main material of the refractory raw material mixture, but the large coarse particles are not included in the refractory raw material mixture of the present invention. In other words, in the castable material of the present invention, the large coarse particles are added in an outer percentage relative to 100% by mass of the refractory raw material mixture. In other words, the refractory raw material mixture of the present invention is a mixture of refractory raw materials with a particle size of less than 8 mm. EXAMPLES

[0018] The raw material blends and evaluation results of the examples of the present invention and the comparative examples are shown in Table 1. The evaluation items and evaluation methods in the examples and the comparative examples are as follows.

[0019] <Alkaline penetration resistance> A predetermined amount of water was added to the raw material mixture of each example and kneaded, and a crucible test piece was obtained by drilling a hole of φ30×35 mm in a prism-shaped test piece of 70×70×65 mm. 20 g of sodium carbonate (commercially available) was placed in the hole of this crucible test piece, and a heat treatment was performed at 1200°C for 12 hours. After the heat treatment, it was allowed to cool (naturally cooled) to room temperature, and then cut at the center of the crucible test piece (axial cross section of the hole), and the cut surface was observed. In the observation of the cut surface, the remaining thickness of the maximum erosion site was measured, and the remaining ratio relative to the thickness before the test was calculated. The alkali penetration resistance was evaluated by an erosion index when the remaining ratio of Comparative Example 1 was set to 100. The smaller the corrosion index, the better the resistance to alkaline penetration, that is, the greater the effect of suppressing alkaline penetration due to alkaline attack. Corrosion index values ​​of less than 80 were evaluated as ◎ (good), between 80 and 90 as ○ (passable), between 90 and 100 as △ (unacceptable), and over 100 as × (poor).

[0020] <Explosion resistance> A prescribed amount of water was added to the raw material mixture of each example, and the mixture was kneaded, poured into a cylindrical mold of 100 mmφ×100 mmh, cured for 24 hours, and removed from the mold to obtain two cylindrical test pieces. Each test piece was heated in an electric furnace at 900°C and held for 30 minutes before being removed. The test pieces were then examined for the presence or absence of explosion and cracking and evaluated. In the evaluation, two test pieces were evaluated, with ◎ (good) for no cracking, 〇 (passable) for microcracks, △ (unacceptable) for partial breakage of the surface layer, and × (poor) for breakage or damage of 50% or more. The inventors have confirmed that if the evaluation of explosion resistance is ◎ (good) or 〇 (passable), a drying process is not required after pouring in an actual furnace.

[0021] <Wear resistance> A specified amount of water was added to the raw material mixture of each example, and the mixture was kneaded, poured into a 115×115×65 mm mold, cured for 24 hours, removed from the mold, and dried to obtain a test piece, which was then heat-treated at 800°C for 5 hours in advance. The test piece was measured in accordance with ASTM C704 (Abrasion Resistance of Refractory Materials at Room Temperature). Specifically, the 115×115 mm surface was set at an inclination of 45° with respect to the direction of the abrasive material discharge. Then, while rotating the test piece at 15 revolutions per minute with the vertical center line of the 115×115 mm surface as the axis, 1 kg of the abrasive material was continuously sprayed onto the 115×115 mm surface. Silicon carbide particles with a particle size adjusted to 1 to 0.3 mm were used as the abrasive material. The spray air pressure was 0.4 MPa. The mass of the test piece before and after the test was measured, and the abrasion volume was calculated from the change in mass and the bulk specific gravity of the test piece. The abrasion resistance was evaluated by the abrasion index when the abrasion volume of Comparative Example 1 was set to 100. The smaller the abrasion index, the better the abrasion resistance, i.e., the greater the effect of suppressing physical impact from objects inside the furnace. The abrasion index of less than 80 was evaluated as ⊚ (good), 80 to less than 90 as ◯ (passable), 90 to less than 100 as △ (unacceptable), and 100 or more as × (poor).

[0022] <Overall rating> When the resistance to alkali penetration, explosion resistance, and abrasion resistance were all rated as ⊚, they were rated as ⊚ (good), when at least one of these ratings was ⊚, they were rated as ⊚ (passable), when at least one of these ratings was △, they were △ (not acceptable), and when at least one of these ratings was ×, they were rated as × (bad). In other words, the overall rating was ranked in the order of ⊚, ⊚, △, and ×, with ⊚ and ⊚ being pass, and △ and × being fail.

[0023] [Table 1]

[0024] Examples 1 to 6 are examples in which the main material of the refractory raw material mixture is an alumina raw material, and the content of silica flour is changed within the range of the present invention. The overall evaluation was ◎ or ◯, and good results were obtained. Among them, Examples 2 to 4 and 6, in which the content of silica flour is within the preferred range of 3 mass% to 10 mass%, were overall evaluated as ◎, and particularly good results were obtained. On the other hand, Comparative Example 1 is an example in which the content of silica flour is below the lower limit of the present invention, and the alkali penetration resistance and abrasion resistance are greatly reduced. Also, Comparative Example 2 is an example in which the content of silica flour is above the upper limit of the present invention, and the explosion resistance is greatly reduced and the abrasion resistance is also insufficient.

[0025] Example 7 is an example containing 0.5% by mass of CaO component derived from alumina cement. Compared to Example 6 which does not contain CaO component derived from alumina cement, the alkali penetration resistance and explosion resistance were slightly lower but still at an acceptable level. In contrast, Comparative Example 3 is an example in which the content of CaO component derived from alumina cement is 1% by mass, which exceeds the upper limit of the present invention, and the alkali penetration resistance and explosion resistance were significantly lowered.

[0026] Example 8 is an example that does not contain calcined alumina. Compared to Example 6 that contains calcined alumina, the alkali penetration resistance and wear resistance were slightly lower, but were still at an acceptable level. Examples 9 and 10 are examples in which the content of calcined alumina was changed, but like Example 6, the overall evaluation was ⊚, and good results were obtained.

[0027] In Examples 11 to 13, the main component of the refractory raw material mixture was changed, but all of them were within the scope of the present invention and good results were obtained. Furthermore, a comparison between Examples 12 and 13 revealed that when the main component of the refractory raw material mixture was a silicon carbide raw material, good results could be obtained even without containing calcined alumina.

[0028] Examples 14 to 16 are examples in which the main component of the refractory raw material mixture is an alumina raw material, and the addition rate of colloidal silica is changed within the range of the present invention. The overall evaluation was ◎ or ◯, and good results were obtained. Among them, Examples 15 and 16, in which the addition rate of colloidal silica is within the preferable range of 1.5 mass% or more and 5 mass% or less, were overall evaluated as ◎, and particularly good results were obtained. In contrast, Comparative Example 4 is an example in which the content of colloidal silica is below the lower limit of the present invention, and the abrasion resistance is significantly reduced and the alkali penetration resistance is also insufficient.Comparative Example 5 is an example in which the content of colloidal silica is above the upper limit of the present invention, and the alkali penetration resistance and abrasion resistance are significantly reduced.

Claims

1. A refractory raw material mixture containing at least one of an alumina raw material, an alumina silica raw material, and a silicon carbide raw material in a total amount of 75% by mass or more, and 1% by mass to 15% by mass or less of silica flour, and having a content of CaO component derived from alumina cement of 0.5% by mass or less (including zero), is added with colloidal silica and SiO 2 A pouring material for a firing furnace, comprising a component added at an addition rate of 0.5 mass% or more and 5 mass% or less.

2. 2. The pourable material for a firing furnace according to claim 1, wherein the refractory raw material mixture contains 4 mass % or more and 10 mass % or less of calcined alumina.

3. The incinerator pourable material according to claim 1 or 2, wherein the silica flour content is 3% by mass or more and 10% by mass or less.

4. The addition rate of colloidal silica is SiO 2 The incinerator pourable material according to claim 1 or 2, wherein the component is 1.5% by mass or more and 5% by mass or less.

Citation Information

Patent Citations

  • Alumina-magnesia based monolithic refractory for casting

    JP1996268769A

  • Silica-based castable refractory and silica-based precast block refractory

    JP2013189322A

  • Castable amorphous refractory

    JP2018111612A

  • Castable refractory

    JP2021109783A

  • High alumina castable and waste processing furnace

    JP2021160950A